Effects of plasma-treatment on the electrical and optoelectronic properties of layered black phosphorus. (September 2018) - Kuriakose, Sruthi; Ahmed, Taimur; Balendhran, Sivacarendran; Collis, Gavin E.; Bansal, Vipul; Aharonovich, Igor; Sriram, Sharath; Bhaskaran, Madhu; Walia, Sumeet
Graphical abstract: We investigate the influence of Ar and O2 plasma on the electrical and optoelectronic properties of plasma-treated BP flakes. It is revealed that by manipulating the environment under which BP is exposed to the plasma, it is possible to engineer defects that lead to new photoluminescence (PL) emission peaks without compromising the switching ratios or carrier mobilities of BP-based field effect transistors (FETs). Overall, our study finds the use of O2 plasma as a more suitable approach to retain and enrich the intrinsic (opto)electronic properties of BP. Highlights: Manipulation of optoelectronic properties of BP by controlling plasma environment. An understanding of plasma environment effects on BP properties. Engineering defects for new photoluminescence (PL) emission peaks. Abstract: Exfoliated few-layer black-phosphorus (BP) has been explored for a variety of electrical and optoelectronic applications. Plasma-assisted thinning of BP has emerged as an exciting pathway to achieve BP crystals of desired thickness. However, to fully realise the true potential of plasma-assisted thinning of BP and other emerging 2D materials, it is critical to understand the effects of different plasma environments on the electrical and optoelectronic properties of the resultant material. Here, we investigate the influence of Ar and O2 plasma on the electrical and optoelectronic properties of plasma-treated BP flakes. It is revealed that by manipulating the environment under which BP is exposed to the plasma, it is possible to engineer defects that lead to new photoluminescence (PL) emission peaks without compromising the switching ratios or carrier mobilities of BP-based field effect transistors (FETs). Overall, our study finds the use of O2 plasma as a more suitable approach to retain and enrich the intrinsic (opto)electronic properties of BP. Additionally, our study, for the first time, experimentally reveals the ability of BP to respond to UV excitation.